2011
DOI: 10.2514/1.j050760
|View full text |Cite
|
Sign up to set email alerts
|

Microvortex Generators Applied to a Flowfield Containing a Normal Shock Wave and Diffuser

Abstract: The flow through a terminating shock wave and the subsequent subsonic diffuser typically found in supersonic inlets has been simulated using a small-scale wind tunnel. Experiments have been conducted at an inflow Mach number of 1.4 using a dual-channel working section to produce a steady near-normal shock wave. The setup was designed so that the location of the shock wave could be varied relative to the diffuser. As the near-normal shock wave was moved downstream and into the diffuser, an increasingly distorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Traditional vortex generators [4] which have the same order of magnitude with boundary layer thickness have been used in supersonic flow control for a long time. Researchers subsequently found that vortex generators which have smaller scale than boundary layer thickness have the advantage of smaller resistance while maintaining the ability of flow control [5,6]. In recent years, microvortex generators have obtained the full attention and development [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…Traditional vortex generators [4] which have the same order of magnitude with boundary layer thickness have been used in supersonic flow control for a long time. Researchers subsequently found that vortex generators which have smaller scale than boundary layer thickness have the advantage of smaller resistance while maintaining the ability of flow control [5,6]. In recent years, microvortex generators have obtained the full attention and development [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…In the follow-up study of Titchener & Babinsky [48], a shock holder was installed above the expansion corner in order to stabilize the normal shock wave. The Mach number was changed to Ma=1.4 and the shock wave was positioned exactly at the entrance of the expansion corner.…”
Section: Slip Linementioning
confidence: 99%
“…A number of baseline experimental studies have been carried out to investigate the effectiveness of MVGs towards SWBLI involving oblique or normal shock waves [7][8][9] and positive effects were confirmed.…”
Section: Introductionmentioning
confidence: 99%